Laparoscopic high uterosacral ligament suspension (modified Shull technique): A case series and a step by step description of surgical procedure. (October 2020) - Vacca, Lorenzo; Lucidi, Alessandro; Panico, Giovanni; Campagna, Giuseppe; Restaino, Stefano; Ercoli, Alfredo; Scambia, Giovanni; Fanfani, Francesco
Abstract: Objective: In this series we investigate the safety, feasibility and efficacy of our laparoscopic modified Shull technique describing the fundamental aspects of this surgical procedure in order to add a new feasible abdominal approach for apex resuspension. Study design: A retrospective case series of 10 patients referring to our Urogynecological department for symptomatic apical prolapse, enrolled consecutively between September 2018 and November 2018. All women underwent the presented technique which we described in detail explaining the fundamental tips and tricks of our procedure. We examined perioperative details, postoperative complication- evaluated with Clavien–Dindo's classification-, anatomical outcome and subjective satisfaction, assessed with the Patient Global Impression of Improvement questionnaire. Results: All women presented symptomatic apical prolapse of II-III grade. No perioperative complications including ureteral damages were recorded. There was only one case of de novo stress urinary incontinence. At 1-year follow-up the POP-Q apex was well suspended in all women with only 2 cases of asymptomatic anterior recurrence. All patients reported a complete resolution of pelvic organ prolapse (POP)-related symptoms and were fully satisfied with the treatment received. Conclusion: Laparoscopic modified Shull technique suggests safety, feasible and efficacy in the treatment of apical prolapse. In addition, this report represents a useful instrument for surgeon to understand key aspects of this surgical procedure allowing to him to perform the described technique in a safe and timely manner.